Ekspor dan Impor Barang Serta Perpajakan Bagi Pelaku Usaha UMKM - Sahdan Maulana; Ayu Fitrianingrum; Abieza Satya Damara; Enno Astri Quinta; Evie Puspita Sari; Kartiko Hariputra; M. Ilham Mu’arief; Utari Ayuningrum Zuti; Taufik Raharjo (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2020)
The object of this community service activity is the Micro-Small Business, Banana Chips Karya Mandiri. The purpose of this community service activity is to provide a basic understanding and foster awareness of business people, especially the object of the Banana Karya Karya Mandiri, in fulfilling tax obligations and providing information related to the export or import of goods that can be carried out in connection with the business being run. These community service activities are divided into two main sub-categories namely taxation and export / import of goods. For sub-taxation activities carried out in the form of an explanation related to tax obligations that must be carried out by the SME business include registration as a taxpayer, calculation of the amount of tax owed (as currently regulated in PP 23), depositing the tax owed to the state treasury and reporting annual tax return, provides an overview of the role of taxes generated from the SME business in the realization of state revenue from the taxation sector year on year, as well as the importance of taxes for the country's development. As for the sub-export / import of goods, the activities carried out are the socialization of Import and / or Export of Personal Goods and Goods for Business Entities, passenger luggage and shipments from and abroad, as well as material on hajj luggage. The results of this service are providing knowledge / education about taxation for MSMEs as well as providing knowledge / education regarding the provisions on the import and / or export of personal goods and goods for business entities as well as the provisions for hajj and umrah luggage.